Influence of Board Characteristics on Carbon Emission Disclosure: Evidence from the Nigerian Oil and Gas Sector - Ezekiel, Oyerogba; Olugbenro, Sunday; Omojola, Sunday; Wright, Olatunde; Aregbesola, Olateju (International Journal of Energy Economics and Policy, 2024)
This study investigates whether board characteristics influence a firm’s carbon emission disclosure, in the context of the Nigerian listed oil and gas companies. Board characteristics is divided into board composition (board size, board independence and board structure) and board diversity (board gender diversity, ethnicity and background). The study assessed data from 22 quoted oil and gas companies for the fifteen-year period (2009-2023). The study adopted ordered regression for data analysis and concludes that board structure, board independence, board gender diversity and board ethnicity significantly influence the likelihood of high-quality carbon emission disclosure. The findings established the significant roles of the board in allocating resources to environmentally friendly activities, monitoring managerial activities, and ensuring that firms meet its obligation to operate in a climate friendly manner.